Pengembangan Penggunaan Media Wall Chart dalam Menulis Karangan Argumentasi - Nurunia Zendrato; Yulismarwina Waruwu; Lorewina Zalukhu; Yunulisman Telaumbanua; Arozatulo Bawamenewi (Departement of Mathematics Education, 2023)
This study aims to determine the effect of using wall chart media. Teaching tool is anything that can be used in the teaching and learning activity to communicate messages or information so that it can stimulate students’ attention and interest in learning. One of the learning process is selection of learning media wall chart. Wall Chart is a teaching tool that might be in the form of floor plans. Charts or schematics that are usually hung on the classroom wall. An online questionnaire served as the study's method of gathering data.. This study obtained the results of a feasibility test with a percentage of 85% by material experts stating that Wall Chart was possible to employ